Determinants of Return On Asset (ROA) at Sharia Commercial Banks 2016 – 2021 - Muhammad Irwin Muslimin; Nurwahidin; Mulawarman Hannase (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2023)
ROA is a ratio that serves to assess a company's ability to make a profit. The amount of ROA can be influenced by many things such as NPF, FDR, and CAR. This study aims to find the effect of NPF, FDR, and CAR on ROA at Islamic Commercial Banks (BUS) in 2016-2021. This research uses a two-stage analysis. The first stage will use multiple linear analysis with the Ordinary Least Square method to find the influence between variables, then the second stage will examine the ROA scheme in Islamic banking, and whether it is in accordance with Islamic principles. The results showed that NPF had a significant negative impact on ROA, FDR had an insignificant positive impact on ROA, and CAR had a significant positive impact on ROA. The results of the calculation of the coefficient of determination show that NPF, FDR, and CAR affect ROA by 78.78% while the rest is explained by other variables that are not taken into account in the study. In addition, the ROA business scheme is in accordance with existing Sharia aspects because nothing is violated in Sharia principles, and the existence of DPS is one of the factors the researchers believe that this business model is in accordance with Sharia values. This research is useful to determine the effect between ROA variables and to find out whether business schemes with ROA are in accordance with Sharia.